A Review of the Components of the Medium-Term National Action Agenda on Productivity 2000-2004: Infrastructure - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2001)
The availability of adequate, reliable and affordable infrastructure is critical to increasing the productivity of Philippine industries and households. Thus, the Medium-Term National Action Agenda for Productivity (MTNAAP) 2000-2004 seeks to contribute towards a) Increasing the provision of basic infrastructure support, especially in the countryside; b) Encouraging private sector participation within an efficient regulatory framework; and c) Strengthening LGUs capability in tapping private sector resources. In order to support the MTNAAPs objectives, it is suggested that the following steps be undertaken: a) Conduct a review of the investment policy in infrastructure b) Estimate relevant price and income elasticities of demand for infrastructure services, and c) Develop quality standards as well as cost and performance indicators for benchmarking.
Keywords: 330; infrastructure; Haushaltsplanung; Produktivität; Philippinen